Participation of Community in Rural Development in Oengkolaki Village Mawasangka District Central Buton Regency - Muslimin; Muhammad Arsyad; Sarmadan (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
The purpose of this study was to determine the kinds of community participation and the factors driving community participation in rural development in Oengkolaki Village, Mawasangka District, Buton Tengah Regency. This type of research is descriptive qualitative with data collection techniques through literature review and field research conducted through observation, interviews, and documentation. After the data has been redundant, then completed the analysis by using qualitative techniques. The results of the study aimed that the form of community participation in rural development in Oengkolaki Village, Mawasangka District, Buton Tengah Regency included participation in development planning, development implementation, and participating in utilizing the results of development. The factors driving community participation in development are awareness, community capacity, and rising community income.